The effect of otitis media with effusion (OME) on emerging literacy : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Education, Massey University - Drumm, Diana (Massey University, 1994)
Otitis Media with Effusion (OME), commonly referred to as glue ear, is one of the most common illnesses of early childhood. It is difficult to detect as OME is frequently symptom free and usually clears spontaneously. It can be detected by tympanometry, a simple painless non intrusive test, which can be easily performed by trained operators. In New Zealand all children have this hearing test on school entry. Research has shown links between OME and educational under achievement, possibly due to the intermittent deafness which accompanies this condition. As OME mostly occurs during early childhood, a time when the basis of language is being established, it may cause delays in learning which will not be seen until later in life. This research was designed to examine the possible effect of OME on emerging literacy in 120 children from a large urban area of New Zealand. The aural history of the children was established from a questionnaire and the results of the hearing tests on school entry. Measures of their reading ability were obtained from their scores on the Diagnostic Reading Survey. This survey, usually referred to as the six year old net test, is taken by most children in New Zealand. The childrens' scores on the reading test were examined to see if there was any correlation between these and evidence of OME. Although no conclusive proof was found that children with OME were reading at a lower age than their peers, statistically significant differences were found between the scores of the Dictation section of the test. The Dictation section is designed to measure how well children are distinguishing and recording individual sounds in words. The findings suggest that OME affects auditory discrimination so that incorrect symbols are ascribed to sounds. This effect will hinder a child when learning to read and may cause delays in other aspects of learning. No evidence of increased incidence of OME amongst Maori or Pacific Island students was found, however, the number of these students in the sample was very small. Maori and Pacific Island students however did have significantly lower scores than their peers in all aspects of the reading test.
Keywords: New Zealand; Deaf children -- Language; Hearing disorders in children; Language acquisition; Otitis media in children